Permian palynostratigraphy of the Claromecó Basin, Argentina - Balarino, María Lucía (2014)
The first palynozonation for Permian strata of the Claromecó Basin (Argentina) is formally proposed, based on palynological assemblages recovered from the UTAL.CMM1 La Estrella.x-1 and UTAL.CMM1 Cruz de Sur.x-1 boreholes, drilled on the Argentinian Continental Platform and correlation with established zones from neighbouring basins. Fifty-five samples were analyzed and 131 species identified from two biozones. The lower Converrucosisporites confluens-Vittatina vittifera (CV) Zone occurs in the Piedra Azul and Bonete formations of both boreholes. This zone can be assigned a Cisuralian-Guadalupian age. The upper Tornopollenites toreutos-Reduviasporonites chalastus (TC) Zone registered in the Tunas Formation can be assigned a Guadalupian-Lopingian age. The CV Zone is dominated by diverse non-taeniate bisaccate, plicate and taeniate pollen. Monosaccate and monosulcate pollen, algae and acritarchs are poorly represented in both biozones. The composition of the TC Zone is broadly similar to the CV Zone, but bisaccate pollen grains are markedly more diverse and abundant in the former.